Histone Modifications in Acute Kidney Injury - Jun Wang; Fengchen Shen; Feng Liu; Shougang Zhuang (Karger Publishers, 2022)
Background: Acute kidney injury( AKI) is a serious clinical problem associated with high morbidity and mortality worldwide. The pathophysiology and pathogenesis of AKI is complex and multifactorial. In recent years, epigenetics has emerged as an important regulatory mechanism in AKI. Summary: There are several types of histone modification, including methylation, acetylation, phosphorylation, crotonylation, citrullination, and sumoylation. Histone modifications are associated with the transcription of many genes and activation of multiple signaling pathways that contribute to the pathogenesis of AKI. Thus, targeting histone modification may offer novel strategies to protect kidneys from AKI and enhance kidney repair and recovery. In this review, we summarize recent advances on the modification, regulation, and implication of histone modifications in AKI. Key Messages: Histone modifications contribute to the pathogenesis of AKI. Understanding of epigenetic regulation in AKI will aid in establishing the utility of pharmacologic targeting of histone modification as a potential novel therapy for AKI.